Isolation and Characterization of Arsenic-Binding Siderophores from Rhodococcus Erythropolis s43 Role of Heterobactin B and Other Heterobactin Variants - Modak-Canobra, B; Levican-Jaque, G; Olguin-Gonzalez, A; Retamal-Morales, G (Springer Science and Business Media Deutschland GmbH, 2021)
Abstract: Rhodococcus erythropolis S43 is an arsenic-tolerant actinobacterium isolated from an arsenic contaminated soil. It has been shown to produce siderophores when exposed to iron-depleting conditions. In this work, strain S43 was shown to have the putative heterobactin production cluster htbABCDEFGHIJ(K). To induce siderophore production, the strain was cultured in iron-depleted medium in presence and absence of sodium arsenite. The metabolites produced by S43 in the colorimetric CAS and As-mCAS assays, respectively, showed iron- and arsenic-binding properties reaching a chelating activity equivalent to 1.6 mM of desferroxamine B in the supernatant of the culture without arsenite. By solid-phase extraction and two subsequent HPLC separations from both cultures, several fractions were obtained, which contained CAS and As-mCAS activity and which were submitted to LC-MS analyses including fragmentation of the major peaks. The mixed-type siderophore heterobactin B occurred in all analyzed fractions, and the mass of the “Carrano heterobactin A” was detected as well. In addition, generation of a molecular network based on fragment spectra revealed the occurrence of several other compounds with heterobactin-like structures, among them a heterobactin B variant with an additional CH2O moiety. 1H NMR analyses obtained for preparations from the first HPLC step showed signals of heterobactin B and of “Carrano heterobactin A” with different relative amounts in all three samples. In summary, our results reveal that in R. erythropolis S43, a pool of heterobactin variants is responsible for the iron- and arsenic-binding activities. Key points: • Several heterobactin variants are the arsenic-binding compounds in Rhodococcus erythropolis S43. • Heterobactin B and the compound designated heterobactin A by Carrano are of importance. • In addition, other heterobactins with ornithine in the backbone exist, e.g., the new heterobactin C. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.